MicroRNA expression profiling and biomarker validation in treatment-naïve and drug resistant non-small cell lung cancer - MacDonagh, Lauren (Transl Lung Cancer Res, 2021)
BACKGROUND: In the absence of targetable mutations or immune checkpoints, cisplatin-doublet chemotherapy remains the standard of care in non-small cell lung cancer (NSCLC). Drug resistance has however become a significant clinical challenge. Exploring a role for small non-coding microRNAs (miRNA) as biomarker candidates in cisplatin resistant (CisR) lung cancer is lacking and warrants further investigation. METHODS: miRNA expression profiling was assessed in a panel of cisplatin sensitive and resistant NSCLC cell lines and validated by qPCR. Modulation of altered miRNAs was studied using antagomiRs and pre-miRs while functional assays were used to assess cisplatin response. The translational relevance of these miRNAs as potential biomarkers was assessed in serum and matched normal and tumour lung tissues from chemo-naïve NSCLC patients, in addition to xenograft formalin-fixed paraffin-embedded (FFPE) tumours derived from cisplatin sensitive and resistant cell lines. RESULTS: Differential expression of a 5-miR signature (miR-30a-3p, miR-30b-5p, miR-30c-5p, miR-34a-5p, miR-4286) demonstrated their ability to distinguish between normal and tumour lung tissue and between NSCLC histologies. In squamous cell carcinoma (SqCC), tissue miRNA expression was associated with poor survival. miR-4286 showed promise as a blood-based diagnostic biomarker that could distinguish between adenocarcinoma and SqCC histologies. In a xenograft model of cisplatin resistance, using 7-9 week old female NOD/SCID mice (NOD.CB17-Prkdcscid/NCrCrl), a 5-miRNA panel showed altered expression between sensitive and resistant tumours. CONCLUSIONS: This study identified a panel of miRNAs which may have diagnostic and prognostic potential as novel biomarkers in lung cancer and furthermore, may have a predictive role in monitoring the emergence of resistance to cisplatin.